MANAGEMENT OF SCHOOL LITERACY MOVEMENT (GLS) PROGRAM IN DEVELOPING INTEREST IN LITERACY AMONG STUDENTS - Alfia Ainun Nikmah; Masturin; Ashif Az Zafi (Universitas PGRI Palembang, 2025)
This study examines the management of the School Literacy Movement (GLS) in fostering students' literacy interest at Al Ishom Jepara Middle School. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation, then analyzed through data collection, reduction, presentation, and conclusion drawing. The findings show that the GLS program is implemented in three stages: planning, implementation, and evaluation. The planning stage involves setting program objectives, assessing available resources, and forming a GLS team. The implementation stage consists of routine activities such as reading Asmaul Husna, library visits, and Quran recitation, followed by development activities like creating reading corners and wall magazines. The learning stage includes short story writing, Quran reading and writing (BTQ), and scientific extracurricular activities. The evaluation stage indicates that the program has been effective in enhancing students' reading and writing skills. The study concludes that a well-structured GLS program significantly contributes to literacy development. It is recommended that schools continuously optimize resources, encourage student participation, and integrate literacy programs into daily learning activities to sustain long-term literacy interest.